Impacts of soil infiltration and its determinants on water resource management on semiarid conditions - Piraneque-Gambasica, Nelson Virgilio; Aguirre-Forero, Sonia Esperanza; Ordoñez-Thalliens, Laureano José (International Journal of Agricultural and Biological Engineering, 2025)
Infiltration is a critical process within the hydrological cycle and plays a fundamental role in agricultural activity, irrigation design, and soil and water conservation efforts. Various factors, including soil properties, precipitation patterns, and flow conditions, influence this complex process. Therefore, understanding the soil’s hydraulic properties, including infiltration, is essential for efficient water resources management. With this in mind, a field study was carried out to assess soil water infiltration across 33 productive units under semiarid conditions. In each case, the predominant landform was characterized, infiltration rates were measured using a double-ring infiltrometer, and soil samples were collected to determine texture, bulk density, soil organic matter, saturation point, field capacity, and electrical conductivity. Based on these data, the infiltration rate, volumetric moisture content, retained water, irrigation interval, and irrigation time were established. The study revealed that the predominant soil types were inceptisols and entisols, which are commonly associated with landforms such as plains, alluvial plains, hills, foothills, and mountains. Soils in these regions primarily exhibited clayey, sandy loam, and sandy clay loam textures. Infiltration rates varied significantly depending on soil texture, ranging from less than 8.00 cm/h to 18.83 cm/h. Additionally, agricultural activities were found to reduce water infiltration rates, indicating that land use practices have a direct impact on this process. Electrical conductivity had a negative effect on infiltration rates in the study area. This research highlights the variables that influence infiltration across different landforms, textural classes, and infiltration types, demonstrating spatial variation. These findings have important implications for the development of sustainable agricultural systems that promote both water and soil conservation.Keywords: soil and water conservation, sustainable agricultural systems, agricultural land use, soil hydraulic properties, water infiltration, irrigation, semiarid environmentDOI: 10.25165/j.ijabe.20251805.9452Citation: Piraneque-Gambasica N V, AguirreForero S E, Ordoñez-Thalliens L J. Impacts of soil infiltration and its determinants on water resource management in semiarid conditions. Int J Agric & Biol Eng, 2025; 18(5): 205–214.